The Impact of Overtime, Career Development, and Workplace Friendly towards Turnover Intention and Emotional Exhaustion as the Mediation of Variable - Wijayanti, Istiqomah Tri; Indiworo, Hawik Ervina; Setyorini, Noni (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim : This study aims to examine the impact of overtime, career development, and workplace friendliness on employee turnover intention, with emotional exhaustion serving as a mediating variable. Design/Methode/Approach : Quantitative research methodology was employed, utilizing statistical analysis techniques. The population comprised all employees of Matahari Department Semarang exhibiting an intention to resign. A sample of 387 employees was selected using the Slovin formula (5% margin of error). Data collection was facilitated through a questionnaire survey administered to the respondents. Partial Least Squares Structural Equation Modeling (PLS-SEM) software was employed for data analysis. Research Finding : The findings indicate that overtime significantly influences emotional exhaustion, while career development does not exhibit a significant impact on emotional exhaustion. Workplace friendliness was found to have a significant effect on emotional exhaustion. Moreover, overtime, career development, and workplace friendliness were identified as influencing factors on turnover intention. Emotional exhaustion was not directly associated with turnover intention but served as a mediator in the relationship between overtime, career development, workplace friendliness, and turnover intention. Specifically, overtime, career development, and workplace friendliness were found to influence turnover intention through their effects on emotional exhaustion.